EFFECTIVENESS OF USING GAMES IN TEACHING GRAMMAR TO YOUNG LEARNERS. ("Conference on Universal Science Research 2023", 2023)
In recent years, the attention to learning and teaching foreign languages is increasing significantly. This requires making foreign language lessons, especially English, interesting, that is, using various innovative methods, technical tools, interactive games that attract different students. The use of such games during the lesson increases the student's enthusiasm for learning science. This article provides information about the effectiveness of using games in teaching grammar to young students.